A national common massive transfusion protocol (MTP) is a feasible and advantageous option for centralized blood services and hospitals. Issue 1 (14th July 2015) - Chay, J.; Koh, M.; Tan, H. H.; Ng, J.; Ng, H. J.; Chia, N.; Kuperan, P.; Tan, J.; Lew, E.; Tan, L. K.; Koh, P. L.; Desouza, K. A.; et al.
Abstract : Background: A common national MTP was jointly implemented in 2011 by the national blood service (Blood Services Group) and seven participating acute hospitals to provide rapid access to transfusion support for massively haemorrhaging patients treated in all acute care hospitals. Methods: Through a systematic clinical workflow, blood components are transfused in a ratio of 1:1:1 (pRBC: whole blood‐derived platelets: FFP), together with cryoprecipitate for fibrinogen replacement. The composition of components for the MTP is fixed, although operational aspects of the MTP can be adapted by individual hospitals to suit local hospital workflow. The MTP could be activated in support of any patient with critical bleeding and at risk of massive transfusion, including trauma and non‐trauma general medical, surgical and obstetric patients. Results: There were 434 activations of the MTP from October 2011 to October 2013. Thirty‐nine per cent were for trauma patients, and 30% were for surgical patients with heavy intra‐operative bleeding, with 25% and 6% for patients with gastrointestinal bleeding and peri‐partum haemorrhage, respectively. Several hospitals reported reduction in mean time between request and arrival of blood. Mean transfusion ratio achieved was one red cell unit: 0·8 FFP units: 0·8 whole blood‐derived platelet units: 0·4 units of cryoprecipitate. Although cryoprecipitate usage more than doubled after introduction of MTP, there was no significant rise in overall red cells, platelet and FFP usage following implementation. Conclusion: This successful collaboration shows that shared transfusion protocols are feasible and potentially advantageous for hospitals sharing a central blood provider.